Evidence for an Association between the SRD5A2 (Type II Steroid 5α-Reductase) Locus and Prostate Cancer in Italian Patients. Issue 3 (2000) - Margiotti, K.; Sangiuolo, F.; De Luca, A.; Froio, F.; Pearce, C. L.; Ricci-Barbini, V.; Micali, F.; Bonafè, M.; Franceschi, C.; Dallapiccola, B.; Novelli, G.; Reichardt, J. K. V.
Abstract : We have investigated the contributions of three polymorphic markers in the SRD5A2 gene to prostate cancer in a group of Italian patients. We have genotyped cases and controls for a polymorphic (TA)n dinucleotide repeat and two functional substitutions, A49T and V89L, substituting respectively alanine with threonine at codon 49, and valine to leucine at codon 89. We found a substantially increased but not significant risk associated with the 49T mutation and a reduction of risk for the V89L substitution. In conclusion, we report on preliminary evidence for both increased and decreased risk associated with separate markers at this locus.